A model for material strengthening under the combined effect of cavitation-bubble collapse and Al2O3 particles, and its test verification - Liu, Lei (Strojniški vestnik, 2021)
A magnesium alloy was subjected to strengthening treatment by coupling cavitation bubbles with Al2O3 nanoparticles. The samples were strengthened by embedding Al2O3 nanoparticles with the energy generated by cavitation-bubble collapse, following which a strengthening model was established to perform test verification. The result showed that, after experiencing the combined effect for 5 min, nanoparticles appear on the sample surface, observed under the scanning electron microscope (SEM); by applying the X-ray diffractometer (XRD) and X-ray photoelectron spectrometer (XPS), it is found that the Al2O3 content increases, implying that Al2O3 particles have been embedded in the sample surface. The microhardness of the samples improves by 36 %. In terms of the strengthening mechanism under the combined effect, the energy generated due to cavitation-bubble collapse is transferred to the Al2O3 particles to enable them to strike the sample surface. Thus, the samples have a more gentle impact, and the transition zone with pits formed on the sample surface is significantly smoother and more continuous. Moreover, the samples are further strengthened after Al2O3 nanoparticles are embedded within the sample surface, as these nanoparticles present high strength and microhardness. However, with the increasing duration of the strengthening process, the failure characteristics of surface morphologies of the samples gradually develop; after experiencing the combined effect for 10 min, a large area of the surface is damaged. XRD and XPS results indicate that Al2O3 particles induce a decrease in the binding capacity with the surface layer of the samples and thus gradually separate from the samples. Therefore, the properties of the samples are adversely affected.
Keywords: cavitation-bubble collapse; coupling; kolaps kavitacijskega mehurčka; mikrotrdota; model utrjevanja; morfologija; nanodelci; nanoparticles; preostale napetosti; sklopitev; strengthening model